Framework to Support Architectural Sustainability using Biomimicry (The Second Level - Merhan Shahda; Ashraf Elmokadem; Mostafa Abd Elhafeez (Port Said Engineering Research Journal, 2014)
Through the study and analysis of the second level to Biomimicry, and try to exploit ways of the organism adapting with its environment, has been reached for the approaches. In this framework, research paper deals with an analysis for the main principles of environmental sustainability in the nature. Research proposed division environmental sustainability principles derived living organisms adapt with nature to four approaches. The aim of this research to submit a proposal for The methodological framework of using the second level of the Biomimicry levels to support architectural sustainability.